Análisis para el mejoramiento logístico para la exportación de concentrado de minerales - Segarra Romero, Juan Carlos (Machala : Universidad Técnica de Machala, 2025)
The mining sector in Ecuador has become a key driver of the national economy, with significant growth in the export of mineral concentrates such as gold and copper. However, this expansion faces major logistical challenges that hinder international competitiveness. This research analyzes deficiencies in the supply chain, emphasizing issues such as poor road infrastructure, port congestion, and bureaucratic customs procedures, all of which cause delays and increase operating costs. A mixed methodology was applied, combining documentary analysis and interviews with industry stakeholders, allowing the identification of critical areas for improvement. The findings reveal that the lack of coordination and communication among supply chain actors—mining companies, carriers, logistics operators, and customs authorities—remains a major obstacle. Likewise, limited technology adoption and resistance to change reduce the efficiency of the export process. Key recommendations include the implementation of integrated information systems, staff training, route optimization, strategic alliances, and continuous performance evaluation of logistics processes. These measures would help reduce costs, streamline procedures, and strengthen competitiveness. In conclusion, improving the logistics of mineral concentrate exports will not only enhance Ecuador’s economic performance but also support sustainable development and consolidate the country’s role as a relevant player in the international mineral trade.
El sector minero en Ecuador se ha consolidado como un pilar fundamental de la economía, con un notable crecimiento en las exportaciones de concentrados de minerales como oro y cobre. Sin embargo, este avance enfrenta importantes desafíos logísticos que limitan la competitividad internacional. La investigación analiza las deficiencias en la cadena de suministro, destacando problemas en la infraestructura vial, la congestión portuaria y la burocracia en los trámites aduaneros, factores que generan retrasos y elevan costos operativos. Se aplicó una metodología mixta, combinando análisis documental y entrevistas a actores del sector, lo que permitió identificar las principales áreas de mejora. Los resultados muestran que la falta de coordinación y comunicación entre los diferentes actores logísticos —mineras, transportistas, operadores y autoridades aduaneras— constituye un obstáculo clave. Asimismo, la limitada adopción de tecnologías y la resistencia al cambio reducen la eficiencia del proceso exportador. Entre las recomendaciones destacan la implementación de sistemas integrados de información, la capacitación del personal, la optimización de rutas, la creación de alianzas estratégicas y la evaluación continua de la cadena logística. Estas acciones permitirían reducir costos, agilizar trámites y fortalecer la competitividad del sector. En conclusión, mejorar la logística de exportación de concentrados de minerales no solo potenciará la economía nacional, sino que también contribuirá a un desarrollo sostenible y a la consolidación de Ecuador como un actor relevante en el comercio internacional de minerales.
Keywords: LOGÍSTICA; MINERÍA; EXPORTACIÓN; COMPETITIVIDAD